Math

posted by .

Differentiate

(1- sinx) / (1 +sinx)

How would I do this?

The answer is (-2cosx)/ (1 + sinx)^2

Thanks in advance :)!!

  • Math -

    d/dx (1-sinx)/(1+sinx)
    [-cosx (1+sinx) - (1-sinx)(cosx)]/(1+sinx)^2

    (-cosx - sinx cosx - cosx + sinx cosx)/(1+sinx)^2
    = -2cosx/(1+sinx)^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig

    prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
  2. Trig........

    I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
  3. check math

    Here are my answers. Can you check if I got the right answers?
  4. math

    the problem is 2cos^2x + sinx-1=0 the directions are to "use an identity to solve each equation on the interval [0,2pi). This is what i've done so far: 2cos^2x+sinx-1=0 2cos^2x-1+sinx=0 cos2x + sinx =0 1 - 2sin^2x + sinx = 0 -2sin^2x+sinx-1=0 …
  5. math

    tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 = 2(1-sin^2x) 2sin^2x + sinx-1=0 (2sinx+1)(sinx-1)=0 x=30 x=270 but if i plug 270 back into the original equation …
  6. math

    solve each equation for 0=/<x=/<2pi sin^2x + 5sinx + 6 = 0?
  7. Trig Help

    Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)] =[sinx+sin^2x]/[sinx+1] =[sinx+(1-cos^2x)]/[sinx+1] =?
  8. trigonometry

    can i use factoring to simplify this trig identity?
  9. Math Help

    Hello! Can someone please check and see if I did this right?
  10. Trigonometry

    How do you simplify: (1/(sin^2x-cos^2x))-(2/cosx-sinx)?

More Similar Questions